Knowledge and Preventive Practices about Hepatitis B and C Virus Infection among Nursing Staffs and Paramedics in Combined Military Hospital, Dhaka - Hamid, Md Abdul; Chowdhury, Mohammed Ali; Shahedul Islam, Saleh Mohammad (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Hepatitis B and C virus infections are important but mostly neglected public health problem in Bangladesh, although a large number of people are suffering from that illness. It is one of the leading cause of morbidity and mortality in the country today. Aim: To assess the level of knowledge and preventive practices regarding hepatitis B and C and to compare between the nursing staffs and paramedics in CMH, Dhaka. Methods: This descriptive cross sectional study was carried out among 141 respondents; 60 nurses and 81 paramedics in CMH, Dhaka from July 2018 to December 2018. All the respondents were interviewed through an interviewer-administered questionnaire. Data were analyzed with SPSS 20. Chi-square test was used to see the level of significance. Results: In this study, 57.4% paramedics had HSC or equivalent educational status, on the other hand among nursing staffs 39.0% had graduate or equivalent and 3.5% had masters or equivalent educational level. Knowledge and preventive practices about hepatitis B and C of nursing staffs was significantly (p<0.05) higher than paramedics. Preventive practice was significantly (p<0.05) associated with status of knowledge. Conclusion: Overall knowledge and preventive practices were found to be acceptable in this study. Most of the nursing staffs and paramedics were at risk of hepatitis B & C. So, appropriate measures needed for further improvement of preventive practices by nursing staffs and especially paramedics. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 54-57